Modified photoanodes by amino-containing phosphonate self-assembled monolayers to improve the efficiency of dye-sensitized solar cells. Issue 55 (20th May 2016) - Lin, Chun-Chu; Cho, Chun-Pei
Abstract : Surface modification by selected molecules to form self-assembled monolayers (SAMs) on the surface of TiO2 electrodes could lower the energy barrier of electron transfer and improve DSSC performance efficiently. Abstract : Surface modification of TiO2 electrodes by selected molecules could lower the energy barrier of electron transfer and improve DSSC performance. The category of the terminal group and molecular length of a self-assembled monolayer influence the surface and interfacial properties of a TiO2 electrode, and the photovoltaic parameters of a DSSC could thereby be adjusted. By electrochemical approaches, it was discovered that the redox current and photocurrent increased when a lower work function and thus a reduced impedance at the TiO2 /dye/electrolyte interface were achieved by using an amino-containing phosphonic acid. However, a smaller photocurrent would be caused when the path for electron transport and charge recombination probability were increased by employing a longer molecule. Both the photocurrent and dark current of a DSSC were suppressed when a larger impedance restrained electron transport through the interface. The TiO2 electrode modified by 2-aminoethylphosphonic acid showed the largest redox current. The corresponding DSSC exhibited the smallest impedance, largest photocurrent and highest efficiency of 6.67%. This study has demonstrated that a monolayer formed on the TiO2 surface by an amino-containing phosphonic acid enhanced DSSC performance efficiently.